PROSES RITUAL KOLOLI KIE ADAT KESULTANAN TERNATE DILIHAT DARI PERSPEKTIF TEORI INTERAKSI SIMBOLIK - Lisda Ariani Simabur; Hafied Cangara (JURNAL BADATI, 2024)
This research discusses the Kololi Kie ritual process, a traditional ceremony of the Sultanate of Ternate, in terms of symbolic interaction theory. The Sultanate of Ternate, as an integral part of Indonesia's cultural heritage, carries outthis ritual as a form of symbolic interaction with the people of Ternate. Symbols such as boats, traditional clothing,traditional music, and historical places are used in rituals to communicate with the community and convey certain meanings and messages. This research uses a qualitative approach with literature studies, exploring supporting sourcesregarding the Kololi Kie ritual process and symbolic interaction theory. The research results show that symbols such as boats, traditional music and historical places play an important role in creating meaning and building relationships between the Sultanate of Ternate and its people. These symbols are also a means of conveying messages aboutprotection, safety and gratitude. In the context of symbolic interaction theory, symbolic communication in the Kololi Kie ritual reflects the community's collective meaning of the greatness of the sultanate and the importance of maintaining ancestral traditions. It is hoped that the results of this research can contribute to further understanding of the role of symbols in cultural rituals and how these symbols play a role in maintaining and passing on cultural valuesfrom one generation to the next.